2002
DOI: 10.1002/ps.522
|View full text |Cite
|
Sign up to set email alerts
|

Computational chemistry study of the environmentally important acid‐catalyzed hydrolysis of atrazine and related 2‐chloro‐s‐triazines

Abstract: Many chlorine-containing pesticides, for example 2-chloro-s-triazines, are of great concern both environmentally and toxicologically. As a result, ascertaining or predicting the fate and transport of these compounds in soils and water is of current interest. Transformation pathways for 2-chloro-s-triazines in the environment include dealkylation, dechlorination (hydrolysis), and ring cleavage. This study explored the feasibility of using computational chemistry, specifically the hybrid density functional theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…21,37 Sawunyama and Bailey in their computational studies on hydrolysis under acidic conditions have shown an important role of the solvation model. 38 However, the activation energy obtained theoretically was in poor agreement with the available experimental values.…”
Section: Energetics Of the Atrazine Hydrolysismentioning
confidence: 75%
See 1 more Smart Citation
“…21,37 Sawunyama and Bailey in their computational studies on hydrolysis under acidic conditions have shown an important role of the solvation model. 38 However, the activation energy obtained theoretically was in poor agreement with the available experimental values.…”
Section: Energetics Of the Atrazine Hydrolysismentioning
confidence: 75%
“…Therefore, chlorine KIE determination seemed to us to be a complementary and necessary tool for the full description of underlying reaction mechanisms. 27,38 The previously determined value of chlorine KIE for the hydrolysis of atrazine at pH 12 was equal to 1.0069. 27 This value indicated significant carbon-chlorine bond elongation in the transition state and was also in agreement with the preliminary theoretically predicted value.…”
Section: Kinetic Isotope Effectsmentioning
confidence: 97%
“…Agriculturally used triazines can undergo biotic and non-biotic degradation through de-alkylation of amine groups at positions 4 and 6 on the triazine ring, dechlorination, de-amination or hydrolysis of the substituent at 2 [9], and to a lesser extent, even ring cleavage [10][11][12][13], to variety of derivatives. Atrazine, propazine and also their derivatives can accumulate in soil and contaminate ground and surface water as a result.…”
Section: Introductionmentioning
confidence: 99%
“…detected no N-bidealkylation or 2-hydroxylation metabolites in any of the previous systems. However, propazine 2-hydroxy (PP-2OH), which is similarly toxic to the parent triazine, has been identified among the degradation products formed in the natural environment [9]. Because it is hardly metabolized under physiological conditions, PP-2OH may be an effective marker for bioaccumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling has been extensively used for elucidating reactions and reaction mechanisms. Therefore; it can be a very useful tool for understanding and optimizing the dyeing process of cotton. In this study, molecular modeling was used to elucidate the most plausible reaction mechanism of the dihalogenotriazine dyes (Figure ) with methanol and with cotton as well.…”
Section: Introductionmentioning
confidence: 99%